Near-surface motion modeling and wave-following control of AUVs - Yi WANG; Xuan WANG; Jianyao WANG; Xiangheng LI (Zhongguo Jianchuan Yanjiu)
ObjectiveTo address the covert communication requirements of autonomous underwater vehicles (AUVs), this study proposes a near-surface communication mode equipped with a foldable antenna.MethodsUtilizing strip theory to predict the wave forces of regular waves, a five-degree-of-freedom motion equation for the AUV near the water surface is established. Simulation studies on wave-following control of the AUV are conducted using the line-of-sight (LOS) method and PID controllers. ResultsSimulation results demonstrate that the normal tracking stability accuracy of the spatial trajectory is 0.247 6 m, and the vertical tracking stability precision of wave-following motion is 0.232 6 m, indicating satisfactory control performance. Statistical analysis reveals that wave height and frequency significantly impact control effectiveness; larger wave height and frequency result in poorer control outcomes. ConclusionThis study validates the feasibility of wave-following motion for AUVs near the water surface, providing theoretical support for high-covert real-time communication applications.